Poverty and Low Education Lead to Child Marriage in Rumintin Village - Kartika, Norma Yuni; Normelani , Ellyn; Ayuningtyas, Efrinda Ari; Noermartanto, Chintania Azahra Tantri (International Journal for Disaster and Development Interface, 2026)
Child marriage is an obstacle in achieving the 5th goal of the Sustainable Development Goals (SDGs) on eliminating all harmful practices. This paper aims to determine the factors causing child marriage in Rumintin Village. This study uses a quantitative method with a survey of 40 respondents who engaged in child marriage and 40 respondents who did not involve child marriage. Then the univariate, bivariate and multivariate analysis will be conducted. The conclusions in this study are (1) women originating from poor household are at risk of practicing child marriage 9.7 times; (2) women who before marriage had an elementary school education or below are at risk of practicing child marriage 2.7 times; (3) women who have a husband who has an elementary school education or below before marriage are at risk of involving in child marriage 0.5 times; (4) women who come from poor households, have an elementary school education or below and their husbands have an elementary school education or below cause child marriage by 32.9 percent. Green economy-based development is one of the efforts to prevent child marriage and alleviate poverty.